FORMULATION AND EVALUATION OF THE PHYSICAL QUALITY OF NIACINAMIDE GEL PREPARATIONS USING PVP AS A GELLING AGENT - Shohihunnatiq Zulananta; Rifkarosita Putri Ginaris; Alfina Nurrahman (Poltekkes Kemenkes Bandung, 2025)
Niacinamide is the amide form of vitamin B3. Other forms of vitamin B3 include niacin (nicotinic acid). Polyvinylpyrrolidone (PVP) is a biodegradable and air-soluble polymer derived from the monomer N-vinylpyrrolidone. Gels are water-rich preparations and have better potential as topical drug delivery preparations compared to ointments because they are non-sticky, require low energy during formulation, are stable, and have aesthetic value. The purpose of this study was to evaluate the physical qualities of PVP-based niacinamide gel preparations based on physical quality parameters, including organoleptic test, ligninogenicity test, pH test, viscosity test, adhesiveness test, and spreading power test. The method used in this study was an experimental method carried out to determine the physical qualities of a good gel. The results of the study showed that the PVP-based niacinamide gel preparation produced had a thick gel texture, transparent color, odorless, homogeneous, an average pH value of 16.6, an average viscosity value of 2673.6 - 2179.6, an average spreadability value of 6.2 - 6.3, and an average adhesiveness value of 4.67 - 4.46. Based on these results, the PVP-based niacinamide gel preparation had physical quality that met the requirements according to good criteria.